A new freshwater crab of the family Hymenosomatidae MacLeay, 1838 (Crustacea, Decapoda, Brachyura) and an updated review of the hymenosomatid fauna of New Caledonia - Guinot, Danièle; Mazancourt, Valentin de (European Journal of Taxonomy, 2020)
A new genus and species, Richerius marqueti gen. et sp. nov., of a crab of the family Hymenosomatidae MacLeay, 1838 are described from the inland waters of New Caledonia based on several specimens collected in two streams at altitudes of 180 m and 500 m, respectively. Richerius marqueti gen. et sp. nov. was compared to the other freshwater species known in New Caledonia, Odiomaris pilosus (A. Milne-Edwards, 1873), and to species of Amarinus Lucas, 1980, a genus comprising many freshwater species in New Zealand, Australia, Indonesia, the Philippines, and Papua New Guinea, but never recorded in New Caledonia. The barcode fragment of the COI mitochondrial gene was sequenced for seven specimens of R. marqueti gen. et sp. nov., and all sequences were deposited in GenBank. A brief and updated review of the New Caledonian marine and freshwater hymenosmatid fauna is provided.